2004
DOI: 10.1002/zaac.200400268
|View full text |Cite
|
Sign up to set email alerts
|

Ba8Ge43 revisited: a 2a′×2a′×2a′ Superstructure of the Clathrate‐I Type with Full Vacancy Ordering

Abstract: The reinvestigation of the crystal structure of Ba8Ge43□3 (space group $Ia{\bar 3}d$, no. 230; a = 21.3123(5) Å; Z = 8; Pearson symbol cI408) shows a full ordering of the vacancies (□) in the germanium framework. This ordered crystal structure can be considered as a derivative of an ideal “Ba8Ge46” clathrate‐I type structure ($Pm{\bar 3}n$, a′ = a/2) in which three Ge vacancies (per formula unit) are allowed to order in a cubic superstructure with a doubled unit cell parameter (□ at the 24c site, space group $… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
133
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 128 publications
(145 citation statements)
references
References 13 publications
12
133
0
Order By: Relevance
“…Samples are denoted by Al x , for example Al 16 representing Ba 8 Al 16 Ge 30 . Powder x-ray diffraction ͑XRD͒ measurements showed the Al 13 and Al 16 samples to be pure type-I clathrate with no additional phases within experimental resolution, while Al 12 and Al 10 also exhibited a small amount of diamond-phase Ge. Rietveld analysis yielded best fits of Ba 8.0 Al 15.1 Ge 27.8 for the nominal Al 16 sample, and Ba 7.0 Al 12.6 Ge 33.5 for Al 12 .…”
Section: Sample Preparation and Characterizationmentioning
confidence: 89%
See 2 more Smart Citations
“…Samples are denoted by Al x , for example Al 16 representing Ba 8 Al 16 Ge 30 . Powder x-ray diffraction ͑XRD͒ measurements showed the Al 13 and Al 16 samples to be pure type-I clathrate with no additional phases within experimental resolution, while Al 12 and Al 10 also exhibited a small amount of diamond-phase Ge. Rietveld analysis yielded best fits of Ba 8.0 Al 15.1 Ge 27.8 for the nominal Al 16 sample, and Ba 7.0 Al 12.6 Ge 33.5 for Al 12 .…”
Section: Sample Preparation and Characterizationmentioning
confidence: 89%
“…Powder x-ray diffraction ͑XRD͒ measurements showed the Al 13 and Al 16 samples to be pure type-I clathrate with no additional phases within experimental resolution, while Al 12 and Al 10 also exhibited a small amount of diamond-phase Ge. Rietveld analysis yielded best fits of Ba 8.0 Al 15.1 Ge 27.8 for the nominal Al 16 sample, and Ba 7.0 Al 12.6 Ge 33.5 for Al 12 . For Al 16 these yielded 2.0, 5.2, and 7.9 Al atoms on the 6c, 16i, and 24k framework sites respectively in the type-I structure ͑space group Pm3n, #223͒, and for Al 12 , 1.5, 2.0, and 9.1 Al atoms.…”
Section: Sample Preparation and Characterizationmentioning
confidence: 89%
See 1 more Smart Citation
“…Ba 8 Ge 43 h 3 is thermodynamically stable in the temperature range from 770°C to 810°C and cannot be obtained as a pure phase by quenching of sealed reaction containers. 4 To avoid the peritectoid decomposition below 770°C, the elements were placed in a glassy carbon crucible, heated to the melt with an induction furnace, and quenched between two steel plates in less than 1 s to room temperature. The reaction product typically consists of a circular plate, $10 mm in diameter and $1 mm in thickness.…”
Section: Methodsmentioning
confidence: 99%
“…Ba 8 Ge 43 h 3 was originally predicted to show metallic behavior according to the 8-N rule, 3,4 because only 12 of the 16 valence electrons related to the Ba atoms are necessary to satisfy the electronic requirements of 12 Ge anions surrounding three vacancies. Experimentally, it was found that the compound shows semiconducting behavior.…”
Section: Introductionmentioning
confidence: 99%